PENGARUH LITERASI KEUANGAN DIGITAL, HERDING, DAN OVERCONFIDENCE TERHADAP KEPUTUSAN INVESTASI EMAS DIGITAL DI APLIKASI DOMPET DIGITAL DANA DALAM PERSPEKTIF BISNIS ISLAM: (Studi Pada Investor Emas Digital Generasi Z Aplikasi DANA Di Bandar Lampung) - Rendi Aditya Putra; Siska Yuli Anita; Dedi Satriawan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of digital financial literacy, herding behavior, and overconfidence on digital gold investment decisions through the DANA application, viewed from the perspective of Islamic business ethics. A quantitative approach was employed using a survey method and purposive sampling technique. The sample consisted of 100 Generation Z respondents (aged 19–25) residing in Bandar Lampung who have experience investing in digital gold via the DANA platform. Data were collected using a structured Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results show that all independent variables have a positive and significant effect on investment decisions: digital financial literacy (β = 0.375; p < 0.001), herding (β = 0.262; p = 0.009), and overconfidence (β = 0.302; p = 0.001). These findings highlight that young investors’ behavior is influenced not only by cognitive rationality but also by psychological and social dynamics. From an Islamic business perspective, investment decisions must be free from excessive speculation and carried out with fairness and transparency. Therefore, integrating digital literacy with Islamic ethical values is essential to shape investment decisions that are not only financially beneficial but also morally responsible and spiritually rewarding. Investment decisions, in this context, should be grounded in the principles of prudence, justice, and the avoidance of gharar (excessive uncertainty). Thus, it is crucial for the younger generation to enhance their financial literacy and ethical awareness to ensure their investment behavior aligns with Islamic values.